2008
DOI: 10.1080/08941920701818258
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Capital on Residential Water-Affecting Behaviors in a Drought-Prone Australian Community

Abstract: Australians report the second highest rate of water consumption in the industrialised world, despite the continent's generally dry conditions. With researchers suggesting that fostering social capital may encourage people to work together on environmental and sustainable initiatives, this article explores whether social capital, environmental responsibility, and socio-demographic lifestyle factors might predict environmentally-friendly or unfriendly home water use behaviours, specifically gardening and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 23 publications
3
68
0
4
Order By: Relevance
“…Furthermore, in the field of environmental policy, the influence of social capital has been analysed both in collective and individual levels (e.g. Jones et al 2009b;Miller and Buys 2008). In the present article, an analysis in individual level is conducted as it permits the exploration of interactions between citizens and public policy implementation (Heffron 2000).…”
Section: Social Capital and Environmental Policy Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the field of environmental policy, the influence of social capital has been analysed both in collective and individual levels (e.g. Jones et al 2009b;Miller and Buys 2008). In the present article, an analysis in individual level is conducted as it permits the exploration of interactions between citizens and public policy implementation (Heffron 2000).…”
Section: Social Capital and Environmental Policy Implementationmentioning
confidence: 99%
“…Finally, participation in social networks may also have a significant influence. Networks function as channels of information, transmitting knowledge for the possible benefits and costs accompanying the application of a public policy (Jones et al 2009a;Miller and Buys 2008) and thus enforcing the arguments for the need of policy implementation. Furthermore, dense social networks are important in order to increase citizens' participation and awareness regarding environmental issues (Wakefield et al 2006).…”
Section: Social Capital and Environmentally Responsible Behaviourmentioning
confidence: 99%
“…Therefore, it is extremely important to create a longstanding water-saving culture in communities. As discussed earlier, community support, through sociocultural interactions in a community, could exert a strong influence on water-saving practices [5,14,19]. Understanding and being able to shape neighborhood effects might become a useful lever to facilitate initiatives that aim at promoting community engagement.…”
Section: Neighborhood Effectsmentioning
confidence: 99%
“…Dean et al [14] argued that an individual's social context, through social capital, would influence support for water-saving management approaches. The term "social capital" in their study refers to the social connectedness of a community that enables residents to work together collaboratively for mutual benefits [18,19]. Dean et al [14] reported that social capital, measured by participation and membership of community organizations, played an important role in building engagement in water-related issues.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Social capital is a broad construct: it has been described as the factors that 'glue' society together (Edwards, 2004), and defined as 'the social connectedness of a community that enables people, organisations, and communities to work together collaboratively for mutual benefit' (Edwards, 2004;Miller & Buys, 2008). Using the economic analogy of 'capital', social capital is conceptualised as a resource that can be accumulated or drawn upon in times of need (Flora & Flora, 2012).…”
Section: Social Capitalmentioning
confidence: 99%